Developing an engineering laboratory work webCD: non-destructive tests - Woo, Tze Keong (2003)
The development of WebCD application has opened a new horizon for education, especially for an engineering laboratory work where demonstrations of physical phenomena are require. The use of WebCD in an engineering laboratory work is beneficial in several ways - providing learners with an economical, safe and simple way to visualize the dynamic behavior and to explore the various aspect of the actual laboratory work situation. In additional to that, this project is aimed at identifying the critical success factor for engineering laboratory work. Apart from that, features needed in a WebCD development are identified so that an engineering laboratory work WebCD can be developed. The engineering laboratory work WebCD, which was developed based on needs analysis will be evaluated, to examine the extend to which the product fulfills the needs of students and lecturers. Questionnaires distribution method is used where questionnaires are designed based on past researches along with the observations and experiences. 50 students and 10 lecturers from KUiTTHO's engineering department were selected as sample for the first stage of the project, which is needs analysis. 10 lecturers and 20 students from KUiTTHO's mechanical engineering departments were selected as samples for the third stage of the project, which is product evaluation. Through the findings, time management and teaching strategy are the critical success factor for engineering laboratory work. Non-destructive test is taken as an experimental topic for the product development, which is based on the needs analysis findings. Through product evaluation, a conclusion can be arrived at that the product successfully fulfills the needs of students and lecturers in time management and teaching strategy. However, some recommendations were given by the respondents for further research. Further research should be done on enhancing the features of the WebCD such as simulation and chat room. In additional to that, further research on integration of WebCD with an online conferencing should be carried out to further enhance the use of ICT in education.